Palm Oil Milling Effluent (POME) Waste Processing by Using Microalgae Chlamydomonas sp. - Riky Yonas; Uray Irzandi; Hantoro Satriadi; W. Widayat; Marcelinus Christwardana; H. Hadiyanto (BIORE Scientia Publisher, 2022)
Along with the growth in oil palm output, the amount of trash produced will also increase. Every palm oil mill is responsible for the disposal of liquid waste known as palm oil mill effluent (POME). POME includes very high levels of BOD and COD, which may hinder the development of microalgae. Before POME may be utilized as a medium for the growth and development of microalgae, a detailed investigation is required to establish the pretreatment measures necessary to reduce the BOD and COD levels. The purpose of this investigation of POME waste as a substrate for the growth and development of microalgae is to examine the POME processing procedure utilizing wild microalgae. The experimental technique consisted of adding POME and microalgae to the Erlemeyer in accordance with the required proportion. Research demonstrates that POME pond IV waste may be utilized as a substrate for the development of wild microalgae to lower POME waste BOD and COD levels. The variables used were the ratio of POME to microalgae volume and the quantity of nutrients supplied. Microalgae growth at a ratio of 1:4 produced the greatest decreases in BOD and COD, namely 61.66 ppm and 173.33 ppm from 110.6 ppm and 496.67 ppm, respectively. The impact of adding nutrient C at a concentration of 120 ppm led to the greatest decrease of BOD and COD, namely 65.33 ppm and 186.67 ppm, whereas adding nutrient N at a concentration of 40 ppm led to the greatest reduction of BOD and COD, namely 55.41 ppm and 158.33 ppm.